How does the type of subsidization affect investments: Experimental evidence - Hagen Ackermann (Arbeitskreis Quantitative Steuerlehre (arqus), 2015)
I study how different types of subsidization affect investment decisions in a laboratory experiment. Even though the expected pro t is identical in all treatments, I find highly significant differences between them. In particular, when investment alternatives get subsidized with tax credits the willingness to invest in the subsidized alternative increases remarkably. In addition, the willingness to take risks increases in general, when tax credits are introduced. Hence, tax credits might be more effective in promoting investments.
Keywords: C91; D14; H25; 330; behavioral economics; subsidies; tax incentives; distorting subsidization; real investment; risk-taking behavior